Pengaruh Gender Diversity dan Green Accounting terhadap Pengungkapan CSR Pada Perusahaan LQ45 2015-2022 - Azzah Nabila; Sella Nopaleo Sapitri; Tiara Anjellina Putri; Rina Yuniarti (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to investigate the impact of gender diversity and the application of green accounting on the transparency of corporate social responsibility (CSR) disclosure. Focusing on companies listed in the LQ45 index on the Indonesia Stock Exchange for the period 2015–2022, this quantitative study uses a purposive sampling method to assign 9 selected companies as a sample, resulting in a total of 72 observational data. In the analysis model, gender diversity is presented through dummy variables, while green accounting is measured through PROPER ratings, with company size as the control variable. The data sourced from the annual report and sustainability report were processed using panel data regression, where the results of the Chow, Hausman, and Lagrange Multiplier tests determined the Common Effect Model as the most appropriate estimation method. The study's findings show a contrast; on the one hand, the existence of diverse genders does not have a real impact on the breadth of CSR disclosure. But on the other hand, the implementation of green accounting has proven to be a significant and positive driving factor in improving the quality of CSR reports in these elite companies.